Conceptualizations of Peace and Development Among Maranaos - D. BARTOLOME, CLARIBEL (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This study focused on the conceptualizations of peace and development among Maranaos. Relationship between peace and development was likewise explored. Finally, how the government can help in the attainment of peace and countryside development and attitudes towards the creation / implementation of SPCPD were revealed.